Biomechanical analysis on take-off technique of chinese and world-class triple-jumpers - Lu, G.; Wang P. E. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The triple jump is a demanding field event in which a jumper must tolerate extremely high impact forces while maintaining high horizontal speed. The present study was designed to explore the take-off technique how to maintain high horizontal speed and achieve optimize effect in the hop, step and jump phases. The best performance of 8 China triple-jumpers (mean performance was 16.01 m) were videotaped and analyzed. This paper compared the parameter with the technique of 18.29 m jump of Edwards in the 1995 WAC. The results showed that bigger push-off angle at toe off resulted in a high angled trajectory in the hop phase and increasing amortization difficulty of the step phase; earlier knee-bend made for less braking angle and loss of horizontal velocity; in the step and jump phase. Chinese jumpers bend the landing knee actively to lessen the forces from landing but delayed the drive into the push-off phase.